Andre Žid o klasičnom i romantičnom (Philologia, 2021)
Gide does not consider the opposition between classicism and romanticism as an opposition between two literary directions in the history of art but as two systems that have conflicted through the ages of version of poetic art. The struggle between classicism and romanticism exists inside every mind, Gide maintains, underlying that the triumph of order and measure is the triumph of classicism, the principal expression of which is understatement. A work of art is the result of two poetic moments: romantic inspiration and classical creation. Poetic beauty is timeless, and Gide was knowledgeable in the fundamental principles of poetics, the only principles that account for the durability of literary creation. Gide called these principles classical, and the poetic process guided by them he called classicism. The classicists are the true poets; classicism is synonymous with aesthetic value and poetic durability, and the classical poetic principles are the golden rules of the poet's profession and craft.